Pengalaman Pelanggan dan Promosi Penjualan terhadap Niat Pembelian Ulang: Wawasan tentang Minimarket yang Sangat Kompetitif di Jakarta - Fini Yulida; Junaid Ali Saeed Rana; Wenny Candra Mandagie; Restiana Ie Tjoe Linggadjaya (International Journal of Digital Entrepreneurship and Business, 2023)
The retail business sector is highly competitive in Indonesia, so mini-market businesses must seek ways to offer high-quality services to their customers to enhance their experience by providing sales promotions. This study measured the effect of customer experience and sales promotion on the repurchase intention of their customers in the Minimarket retail business in Jakarta – Indonesia. The data was gathered by surveying 150 customers of minimarkets in Jakarta using purposive sampling; the questionnaire was shared through Google forms. Analysis of the data was implemented through SPSS (v.25) and AMOS (v.26). AMOS is used to apply Structured Equation Modeling (SEM). Estimation with SEM is used as a robustness test to see the consistency of results with multiple linear regression. Such a technique provides a research gap and contribution to the literature. The results indicate that customer experience was influenced by 44% of repurchase intention, whereas sales promotion was influenced by 52% of repurchase intention. Therefore, the study accurately assesses that consumer experience and sales promotion collectively impact customers’ repurchase intention by 47% at Jakarta (Indonesia) minimarkets. Retail companies are advised to continue to offer a good service for their customers to enhance their experience while shopping, accompanied by providing the best sales promotions so that customers’ intention to repurchase at that specific minimarket would increase.